Adhesive Sheet
Patent Information
- Application Number
- JP2023500462
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-19
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2041-02-19
Smart Images

Figure 0007634074000005 
Figure 0007634074000006 
Figure 0007634074000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive sheet that maintains a stable, high adhesive strength after heat curing and has excellent temporary fixation properties. [Background technology]
[0002] Epoxy resin adhesives have excellent heat resistance and strong adhesive properties and are therefore widely used in applications such as component bonding and structural bonding.
[0003] On the other hand, there are cases where it is necessary to fill a narrow portion of an industrial part with an adhesive. In such cases, a method is known in which an adhesive sheet made of an adhesive containing a temperature-sensitive foaming agent, or an adhesive sheet having a layer made of such an adhesive on one or both sides of a substrate, is inserted into the narrow portion and heated to foam the adhesive, thereby filling the narrow portion with the adhesive.
[0004] Patent Document 1 describes an adhesive sheet used to fill gaps (narrow areas) with an epoxy adhesive. It explains that when a release agent is applied to the surface of the adhesive layer of this adhesive sheet (i.e., when a release agent layer is formed), the workability when inserting the sheet into the gap is improved.
[0005] Patent Document 2 also describes an adhesive sheet used to fill gaps (narrow areas) with an epoxy adhesive, and explains that if the surface of the adhesive layer is covered with a coating layer that does not exhibit tack at room temperature, the adhesive layer can be prevented from cracking and falling off.
[0006] The release agent layer of Patent Document 1 and the coating layer of Patent Document 2 are mixed with the adhesive layer and disappear when the adhesive sheet is inserted into the gap and heated to foam, and therefore the adhesive performance of the adhesive is not significantly impaired. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2016 / 163514 [Patent Document 2] JP 2016-084470 A Summary of the Invention [Problem to be solved by the invention]
[0008] The inventors have noted that in the applications described above, it is preferable to temporarily fix an adhesive sheet having an epoxy-based adhesive layer to the desired location, insert it into a narrow section, and heat and foam it while keeping the position stable.
[0009] For example, if a liquid epoxy resin is used to impart tackiness to the epoxy adhesive layer, the above-mentioned temporary fixation becomes possible. However, since liquid epoxy resins generally have poor heat resistance, the adhesive layer containing liquid epoxy resin has poor heat resistance, and the environment in which the adhesive sheet can be used is restricted. In addition, since there are few types of liquid epoxy resins available on the market, the range of material selection is narrow. Moreover, the hardness of the adhesive layer decreases, and the shape stability also decreases accordingly, so that, for example, when the adhesive sheet is rolled up, the adhesive may protrude from the end face.
[0010] Furthermore, even if tackiness is imparted to the epoxy adhesive layer, temporary fixation is not possible if the release agent layer of Patent Document 1 or the coating layer exhibiting no tackiness of Patent Document 2 is provided uniformly on the adhesive layer.
[0011] An object of the present invention is to provide an adhesive sheet that has excellent temporary fixation properties (the property exhibiting the adhesive strength required for temporary fixation) while maintaining a stable high adhesive strength after heat curing. [Means for solving the problem]
[0012] As a result of intensive research to achieve the above-mentioned object, the inventors discovered that it is effective to partially provide a pressure-sensitive adhesive region (A2R) on the surface of the adhesive layer (A1L), which is solid at the ambient temperature when handled, and thus completed the present invention.
[0013] That is, the present invention is an adhesive sheet having an adhesive layer (A1L) that is solid at 18°C, wherein the adhesive layer (A1L) contains an epoxy resin, and at least one surface of the adhesive layer (A1L) has an adhesive region (A2R) formed by partially providing an adhesive (A2), and the area on the surface where the adhesive region (A2R) is not formed is an adhesive layer exposed region (A1LR) where the surface of the adhesive layer (A1L) is exposed. Effect of the Invention
[0014] In the present invention, by partially providing a pressure-sensitive adhesive region (A2R) on the surface of the adhesive layer (A1L), which is solid at the ambient temperature during handling, it is possible to provide an adhesive sheet that has excellent temporary fixation properties (properties that exhibit the adhesive strength required for temporary fixation) while maintaining a stable high adhesive strength after heat curing. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic cross-sectional view showing an embodiment of an adhesive sheet of the present invention. [Diagram 2] 1 is a schematic plan view showing an embodiment of an adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described with reference to FIGS. 1(a) to (i).
[0017] The embodiment shown in FIG. 1(a) is an adhesive sheet having a pressure-sensitive adhesive region (A2R) and an exposed adhesive layer region (A1LR) on one side of an adhesive layer (A1L).
[0018] In Fig. 1(a), the adhesive layer (A1L) is a layer formed by the adhesive (A1), specifically containing an epoxy resin. The adhesive layer (A1L) also contains a foaming agent (preferably a temperature-sensitive foaming agent). The adhesive sheet in Fig. 1(a) does not have a substrate, and is a baseless type adhesive sheet whose main component is the adhesive layer (A1L).
[0019] In FIG. 1(a), the adhesive region (A2R) is a region formed by partially providing the adhesive (A2) on one side of the adhesive layer (A1L). The outer surface of the adhesive region (A2R) in FIG. 1(a) protrudes outward from the outer surface of the adhesive layer exposed region (A1LR). This protruding outer surface of the adhesive region (A2R) tends to prevent air from being trapped on the adhesion surface, for example, by discharging air through the space above the adhesive layer exposed region (A1LR) when the adhesive sheet is attached (temporarily fixed). The height from the outer surface of the adhesive layer exposed region (A1LR) to the outer surface of the adhesive region (A2R) is preferably 1 to 10 μm, more preferably 1 to 5 μm.
[0020] In FIG. 1(a), the adhesive layer exposed region (A1LR) is a region on the surface of the adhesive layer (A1L) on the side on which the pressure-sensitive adhesive region (A2R) is formed, where the pressure-sensitive adhesive region (A2R) is not formed.
[0021] The adhesive sheet of the present invention has a pressure-sensitive adhesive region (A2R), so it can be temporarily fixed before heating and foaming, regardless of the physical properties (e.g., tackiness) of the adhesive layer (A1L). Moreover, since it has an adhesive layer exposed region (A1LR), the adhesive layer (A1L) foams when heated, and the swollen adhesive layer (A1L) comes into contact with the adherend. As a result, stable high adhesive strength is achieved after heating and foaming.
[0022] The embodiment shown in FIG. 1(b) is an adhesive sheet in which the outer surface of the adhesive region (A2R) and the outer surface of the adhesive layer exposed region (A1LR) are approximately on the same plane. In the present invention, the term "approximately on the same plane" also includes the case where dimensional variations occur due to manufacturing errors in each region when manufacturing on the same plane. The outer surface of the adhesive region (A2R) in FIG. 1(a) described above protrudes outward from the outer surface of the adhesive layer exposed region (A1LR), but the present invention is not limited to this, and may have a configuration as shown in FIG. 1(b). By having the outer surfaces of both regions approximately on the same plane as shown in FIG. 1(b), for example, the adhesion between the adhesive layer (A1L) and the adhesive region (A2R) is improved, and the adhesive region can be prevented from falling off.
[0023] The embodiment shown in FIG. 1(c) is an adhesive sheet having a pressure-sensitive adhesive region (A2R) on one side of the adhesive layer (A1L) and a substrate 10 on the other side of the adhesive layer (A1L). The adhesive sheet in FIG. 1(a) described above has nothing on a side other than the side having the pressure-sensitive adhesive region (A2R) of the adhesive layer (A1L), but the present invention is not limited to this, and the adhesive sheet may have a substrate 10 as shown in FIG. 1(c). The embodiment shown in FIG. 1(c) is one of the preferred embodiments. By having the substrate 10 in the adhesive sheet, for example, the strength and shape retention of the adhesive sheet are improved.
[0024] The embodiment shown in FIG. 1(d) is an adhesive sheet having a pressure-sensitive adhesive region (A2R) on one side of the adhesive layer (A1L) and a release layer 11 on the other side of the adhesive layer (A1L). The adhesive sheet in FIG. 1(a) described above has nothing on a side other than the side having the pressure-sensitive adhesive region (A2R) of the adhesive layer (A1L), but the present invention is not limited to this, and the release layer 11 may be provided as shown in FIG. 1(d). The embodiment shown in FIG. 1(d) is one of the preferred embodiments. By having the release layer 11 in the adhesive sheet, for example, the adhesive sheet tends to have improved slipperiness when inserted into a narrow portion, making it easier to insert.
[0025] In the above embodiment shown in Fig. 1 (a) to (d), the adhesive layer (A1L) also contains a foaming agent (preferably a temperature-sensitive foaming agent). By containing a foaming agent in the adhesive layer (A1L), for example, the adhesive tends to fill a wider area due to a foaming phenomenon. However, the present invention is not limited thereto, and the adhesive layer may not contain a foaming agent.
[0026] The embodiment shown in FIG. 1(e) is an adhesive sheet having an adhesive layer (A1L) on both sides of the substrate 10. The adhesive sheet in FIG. 1(c) described above has an adhesive layer (A1L) on one side of the substrate 10, but the present invention is not limited thereto, and the adhesive layer (A1L) may be on both sides of the substrate 10 as shown in FIG. 1(e). The embodiment shown in FIG. 1(e) is one of the preferred embodiments. Specifically, this adhesive sheet has an adhesive layer (A1L) on both sides of the substrate 10, and the two adhesive layers (A1L) contain a foaming agent (preferably a temperature-sensitive foaming agent), and the outer surface of one of the two adhesive layers (A1L) has a pressure-sensitive adhesive region (A2R) and an adhesive layer exposed region (A1LR). By having the adhesive layer (A1L) on both sides of the substrate 10, for example, when heated, the adhesive layers (A1L) on both sides of the substrate 10 foam, and the swollen adhesive layer (A1L) comes into contact with the adherend. As a result, stable high adhesive strength is also achieved after heating and foaming.
[0027] The embodiment shown in Fig. 1(f) is an adhesive sheet in which the outer surface of the adhesive region (A2R) and the outer surface of the adhesive layer exposed region (A1LR) are present on approximately the same plane. The outer surface of the adhesive region (A2R) in Fig. 1(e) previously described protrudes outward from the outer surface of the adhesive layer exposed region (A1LR), but the present invention is not limited to this, and may have a configuration as shown in Fig. 1(f) as in Fig. 1(b) previously described. The advantages and preferred height of such a configuration are the same as those described for the configuration in Fig. 1(b).
[0028] The embodiment shown in Fig. 1(g) is an adhesive sheet in which the adhesive layer (A1L) does not contain a foaming agent. The two adhesive layers (A1L) in Fig. 1(e) described above contain a foaming agent (preferably a temperature-sensitive foaming agent), but the present invention is not limited thereto, and the adhesive layer may not contain a foaming agent, as shown in Fig. 1(f). Even in this embodiment, when the epoxy resin becomes fluid due to heating of the adhesive sheet, the epoxy resin can reach the adherend from the pressure-sensitive adhesive layer exposed region (A1LR).
[0029] The embodiment shown in Fig. 1(h) is an adhesive sheet having a pressure-sensitive adhesive region (A2R) and an adhesive layer exposed region (A1LR) on the outer surface of one of the two adhesive layers (A1L), and a release layer 11 on the outer surface of the other adhesive layer (A1L). The outer surface of the other adhesive layer (A1L) in Fig. 1(e) described above has nothing, but the present invention is not limited to this, and as in Fig. 1(d) described above, it may have a release layer 11 as shown in Fig. 1(h). The advantages of such a configuration are the same as those described for the configuration in Fig. 1(d).
[0030] The embodiment shown in Fig. 1(i) is an adhesive sheet having a pressure-sensitive adhesive region (A2R) and an exposed adhesive layer region (A1LR) on the outer surface of two adhesive layers (A1L). In the adhesive sheet in Fig. 1(e) described above, only one adhesive layer (A1L) has each region, but the present invention is not limited to this, and both layers may have a pressure-sensitive adhesive region (A2R) as shown in Fig. 1(i).
[0031] Next, an embodiment of the pattern of the adhesive region will be described with reference to FIGS. 2(a) and (b).
[0032] The pattern of the adhesive region (A2R) is not particularly limited. For example, as shown in FIG. 2(a), it may be a pattern in which round island-shaped adhesive regions (A2R) are regularly arranged in horizontal rows at half-shifted positions, or as shown in FIG. 2(b), it may be a pattern in which square island-shaped adhesive regions (A2R) are regularly arranged in vertical rows at equal intervals, or it may be a pattern in which vertical stripe-shaped adhesive regions (A2R) are regularly arranged at equal intervals. A pattern in which the adhesive regions (A2R) are regularly arranged is preferable, but they may be randomly mixed. Other shapes of the adhesive region (A2R) include, for example, a triangular shape and a polygonal shape.
[0033] The width of the pressure-sensitive adhesive region (A2R) is not particularly limited, but is preferably 0.5 to 5 mm, more preferably 0.5 to 3 mm. The width of the adhesive layer exposed region (A1LR) is not particularly limited, but is preferably 0.1 to 3.0 mm, more preferably 0.1 to 1 mm. Furthermore, when the outer surface of the pressure-sensitive adhesive region (A2R) protrudes outward from the outer surface of the adhesive layer exposed region (A1LR), the height of the protruding portion is not particularly limited, but is preferably 1 to 10 μm, more preferably 1 to 5 μm.
[0034] The ratio of the area of the adhesive region (A2R) to the total area (100%) of the area of the adhesive region (A2R) and the area of the adhesive layer exposed region (A1LR) is preferably 1% to 70%, more preferably 20 to 70%, and particularly preferably 55 to 65%. By providing the adhesive region (A2R) at such a ratio, temporary fixation (a property showing the adhesive strength required for temporary fixation) can be obtained without impeding the fluidity of the adhesive during heat curing.
[0035] [Adhesive layer (A1L)] The adhesive layer (A1L) in the present invention is solid at 18°C, and preferably does not show tack at 5°C. In the present invention, "solid" means that the peak temperature of tan δ obtained by the following measurement method is 18°C or higher. The peak temperature of tan δ of the adhesive layer (A1L) is preferably 20 to 100°C, more preferably 40 to 100°C. In addition, in the present invention, "does not show tack" means that the sheet falls off in the evaluation of low-temperature adhesion described below. When the adhesive layer (A1L) has these properties, shape stability is improved, the adhesive can be prevented from squeezing out when rolling, and the slipperiness when inserting the adhesive sheet can be improved. (Method of measuring peak temperature of tan δ) Using a viscoelasticity testing machine for dynamic viscoelasticity measurements, an adhesive sample with a thickness of approximately 2 mm was sandwiched between the parallel plates of the measuring section of the testing machine, and the storage modulus G' and loss modulus G'' were measured at a frequency of 10 Hz and at temperatures between -20°C and 100°C. Tan δ was calculated using the formula tan δ (loss factor) = G'' / G', and the peak temperature was analyzed.
[0036] The adhesive layer (A1L) in the present invention contains an epoxy resin. This epoxy resin preferably contains a multifunctional epoxy resin. The type of multifunctional epoxy resin is not particularly limited, but a novolac type epoxy resin such as a phenol novolac type or a cresol novolac type, or a mixture thereof is preferred. When a novolac type epoxy resin is used, the glass transition point of the cured product becomes high, so that the adhesive strength tends to be stable even at high temperatures.
[0037] As the epoxy resin, an epoxy resin other than the polyfunctional epoxy resin may be used in combination. By using a mixture of the polyfunctional epoxy resin and the other epoxy resin, the physical properties such as the softening point, melt viscosity, glass transition point, and storage modulus of the epoxy resin can be easily and precisely adjusted. In general, mixing an epoxy resin having a low softening point or in a liquid state can increase the fluidity of the adhesive layer when heated and the flexibility before and after curing. On the other hand, mixing an epoxy resin having a high softening point or in a semi-solid or solid state can reduce the tackiness of the adhesive layer surface. In addition, the liquid epoxy resin can also be used for the purpose of pre-dispersing components such as powdery or granular thermally expandable microcapsules contained in the temperature-sensitive foaming agent, or for the purpose of uniformly mixing the epoxy resin components.
[0038] Specific examples of such mixable epoxy resins include bisphenol-type epoxy resins such as bisphenol A type, dimer acid-modified bisphenol A type, and bisphenol F type; epoxy resins having an aliphatic skeleton such as hexanediol diglycidyl ether; phenoxy resins (polyhydroxy polyethers synthesized from bisphenols and epichlorohydrin); and crystalline epoxy resins. Crystalline epoxy resins are solids that do not show tack at room temperature, whereas their melt viscosity drops significantly above their melting point, so they act as reactive diluents above their melting point. Therefore, when crystalline epoxy resins are included in the adhesive layer (A1L), the fluidity of the adhesive layer (A1L) during heating can be further increased, which acts favorably on the thermal expansion of the adhesive layer (A1L). In addition, since they are solids that do not show tack at room temperature, they are useful for reducing the tackiness of the adhesive layer (A1L) surface or for making the adhesive layer (A1L) surface non-tacky. When the adhesive layer (A1L) is formed by a melt coating method, the melt viscosity of the epoxy resin can be reduced by heating the epoxy resin to a temperature equal to or higher than the melting point of the crystalline epoxy resin, thereby increasing the melt coating speed.
[0039] The number average molecular weight of epoxy resins, calculated using standard polystyrene standards by GPC, is generally 100 to 60,000. The epoxy equivalent of epoxy resins is generally 50 to 30,000 g / eq.
[0040] The curing agent for the epoxy resin used in the adhesive layer (A1L) is not particularly limited, but a phenolic resin is preferred. If a phenolic resin is used as a curing agent in combination with an imidazole-based compound as a curing accelerator described below, the curing time can be shortened and heat resistance can be improved. In addition, the use of a phenolic resin as a curing agent makes it easier to design heat resistance, electrical properties, and the like. The amount of phenolic resin added is determined so that the ratio of the hydroxyl equivalent of the phenolic resin to the epoxy equivalent of the epoxy resin is theoretically about 1:1. The ratio of the hydroxyl equivalent of the phenolic resin to the epoxy equivalent of the epoxy resin is usually 0.5 to 2.0, preferably 0.8 to 1.2.
[0041] The curing accelerator for the epoxy resin used in the adhesive layer (A1L) is not particularly limited, but when a phenolic resin is used as a curing agent, an imidazole-based compound is preferred. If an imidazole-based compound is used as a curing accelerator in combination with a phenolic resin as a curing agent, the curing time can be shortened and heat resistance can be improved. In addition, compared to other curing accelerators, imidazole-based compounds have the advantage that they can be used as a single catalyst and are easy to use because they are available in grades with very fine particle sizes.
[0042] Specific examples of the imidazole-based compound include imidazole derivatives such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 2,4-diethylimidazole, and 2-phenyl-4-methyl-5-hydroxyimidazole. Two or more imidazole-based compounds may be used in combination. Among them, 2-phenyl-4,5-dihydroxymethylimidazole is preferred. The content of the imidazole-based compound is preferably 0.1 to 1.0 parts by mass, more preferably 0.3 to 0.8 parts by mass, based on 100 parts by mass of the resin component in the adhesive layer.
[0043] The adhesive layer (A1L) preferably contains a thermosensitive foaming agent. Examples of the thermosensitive foaming agent include inorganic foaming agents such as ammonium carbonate, ammonium hydrogen carbonate, ammonium nitrite, ammonium borohydride, and azides; organic foaming agents such as fluorinated alkanes such as trichloromonofluoromethane, azo compounds such as azobisisobutyronitrile, hydrazine compounds such as paratoluenesulfonylhydrazide, semicarbazide compounds such as p-toluenesulfonylsemicarbazide, triazole compounds such as 5-morpholyl-1,2,3,4-thiatriazole, and N-nitroso compounds such as N,N-dinitrosoterephthalamide; and thermoexpandable microcapsules obtained by microencapsulating thermoexpandable agents made of hydrocarbon compounds. Two or more thermosensitive foaming agents may be used in combination. When an epoxy resin is used, a thermoexpandable microcapsule is preferred in that it does not inhibit the curing of the epoxy resin and reduces adverse effects on the physical properties of the epoxy resin.
[0044] A thermally expandable microcapsule is a microcapsule that has a shell made of a thermoplastic resin with gas barrier properties and contains a thermal expansion agent inside the shell. When a thermally expandable microcapsule is heated, the thermoplastic resin of the shell softens and the volume of the thermal expansion agent increases, causing the capsule to expand. For example, the vaporization of a low-boiling point hydrocarbon compound can be used to expand the capsule.
[0045] The expansion (foaming) temperature of the thermally expandable microcapsules is preferably equal to or higher than the softening point of the epoxy resin and equal to or lower than the activation temperature of the curing reaction of the epoxy resin. If the foaming temperature is equal to or higher than the softening point of the epoxy resin, the thermal expansion agent can be sufficiently expanded in the softened epoxy resin, and the thickness of the adhesive layer (A1L) after foaming can be made uniform. If the foaming temperature is equal to or lower than the activation temperature of the curing reaction of the epoxy resin, the epoxy resin can be prevented from curing before foaming. Furthermore, by setting the softening point of the epoxy resin to equal to or lower than the activation temperature of the curing reaction, when the manufacturing process of the adhesive sheet includes melting or solution coating, the epoxy resin can be prevented from gelling during these coating steps and the drying steps associated therewith.
[0046] The softening point of the epoxy resin can be measured using the ring and ball softening point test method specified in JIS K 2207. The foaming temperature of the thermally expandable microcapsule is the temperature at which the volume of the thermally expandable microcapsule changes, and can be selected, for example, from the range of 70°C to 200°C, preferably 100°C to 180°C.
[0047] The content and volume expansion coefficient of the thermosensitive foaming agent can be appropriately determined depending on the strength and adhesive force required for the cured adhesive layer (A1L), the expansion coefficient required for the adhesive sheet, etc. The content of the thermosensitive foaming agent is preferably 0.5 to 20 parts by mass, more preferably 2 to 15 parts by mass, per 100 parts by mass of the resin component in the adhesive layer (A1L). The thickness increase factor of the adhesive sheet after foaming can be, for example, 1.1 times or more and 10 times or less.
[0048] The particle size of the heat-sensitive foaming agent may be appropriately selected depending on the thickness of the adhesive layer (A1L), and specifically, the average particle size is preferably about 5 to 20 μm.
[0049] It is preferable to add other resins (heat-resistant resins, etc.) to the adhesive layer (A1L) in terms of adhesion to the substrate, flexibility when the adhesive sheet is folded, leveling when the adhesive is applied, and prevention of dripping when cured by heating. Specific examples of other resins include polyester resins, butyral resins, urethane resins, carboxyl-terminated butadiene nitrile rubber (CTBN), and epoxy-modified butadiene. Among these, urethane resins are most preferable in terms of flexibility and adhesiveness.
[0050] The urethane resin is generally a resin containing a soft segment composed of a polyol monomer unit and a hard segment composed of a polyfunctional isocyanate compound or a low molecular weight glycol monomer unit. The polyol used in the urethane resin is a compound having two or more hydroxyl groups. From the viewpoint of improving properties such as rubber elastic elongation recovery rate, the number of hydroxyl groups in the polyol is preferably 2 to 3, more preferably 2. As the polyol, for example, polyester polyol, polyether polyol, polycaprolactone polyol, polycarbonate polyol, castor oil polyol can be used. Two or more kinds of polyols may be used in combination.
[0051] As the polyfunctional isocyanate compound used as a crosslinking agent for crosslinking the polyol, for example, a polyfunctional aliphatic isocyanate compound, a polyfunctional alicyclic isocyanate compound, or a polyfunctional aromatic isocyanate compound can be used. In addition, a trimethylolpropane adduct of these compounds, a biuret reacted with water, or a trimer having an isocyanurate ring can also be used. Two or more types of polyfunctional isocyanate compounds may be used in combination.
[0052] Specific examples of polyfunctional aliphatic isocyanate compounds include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0053] Specific examples of polyfunctional alicyclic isocyanate compounds include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0054] Specific examples of polyfunctional aromatic isocyanate compounds include phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.
[0055] The urethane resin is obtained by curing the composition containing the polyol and the polyfunctional isocyanate compound described above. In particular, from the viewpoint of properties such as rubber elastic elongation recovery rate, a low crystalline linear polyester polyurethane resin is preferred, and a hexanediol copolyester polyurethane resin or a polytetramethylene glycol polyurethane resin is more preferred.
[0056] The content of the urethane resin is preferably 10 to 60 parts by mass relative to 100 parts by mass of the resin component in the adhesive layer (A1L).
[0057] The adhesive layer (A1L) preferably contains a filler from the viewpoints of heat resistance, thermal conductivity, and reinforcement. The type of filler is not particularly limited, and examples thereof include inorganic fillers such as aluminum oxide, magnesium oxide, calcium oxide, aluminum hydroxide, magnesium hydroxide, boron nitride, silicon nitride, silicon oxide, and talc (magnesium silicate), and fibrous fillers such as milled fiber and chopped fiber. Two or more types of fillers may be used in combination. The content of the filler is preferably 5 to 300 parts by mass, more preferably 10 to 100 parts by mass, based on 100 parts by mass of the thermosetting resin component in the adhesive.
[0058] The adhesive layer (A1L) may contain additives such as antioxidants, such as phenol-based antioxidants and sulfur-based antioxidants, silane coupling agents, such as epoxy-modified alkoxysilanes, thixotropic agents, such as fumed silica, and pigments and dyes for identification, as necessary.
[0059] The thickness of the adhesive layer (A1L) may be appropriately determined depending on the intended use, and is usually 2 to 300 μm, preferably 2 to 150 μm.
[0060] [Adhesive area (A2R)] The adhesive region (A2R) in the present invention is provided for temporary fixation before the adhesive is heated and cured to perform full adhesion.
[0061] In the present invention, the adhesive (A2) constituting the adhesive region (A2R) may be, for example, an acrylic adhesive, a rubber adhesive, or a silicone adhesive. These may be used in combination of two or more kinds.
[0062] The type of acrylic adhesive is not particularly limited, and various known acrylic adhesives having an acrylic copolymer as the main component can be used. For example, the acrylic copolymer can be an acrylic copolymer obtained by copolymerizing a (meth)acrylic acid ester, a carboxyl group-containing monomer, and other monomers as necessary. Specific examples of the (meth)acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, and lauryl (meth)acrylate. Specific examples of carboxyl group-containing monomers include (meth)acrylic acid, itaconic acid, crotonic acid, (anhydrous) maleic acid, fumaric acid, 2-carboxy-1-butene, 2-carboxy-1-pentene, 2-carboxy-1-hexene, and 2-carboxy-1-heptene. Specific examples of other monomers include hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, as well as acrylonitrile, styrene, 2-methylolethylacrylamide, vinyl acetate, and acryloylmorpholine.
[0063] The acrylic copolymer is preferably an acrylic copolymer containing, as polymer chain components, a (meth)acrylic acid alkyl ester (a1) having an alkyl group with 1 to 3 carbon atoms, a (meth)acrylic acid alkyl ester (a2) having an alkyl group with 4 to 12 carbon atoms, a carboxyl group-containing monomer (a3), a hydroxyl group-containing monomer (a4), and vinyl acetate (a5).
[0064] Specific examples of the (meth)acrylic acid alkyl ester (a1) having an alkyl group having 1 to 3 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate. Among these, methyl (meth)acrylate is preferred. The content of the (meth)acrylic acid alkyl ester (A1) is 10 to 20 mass%, preferably 12 to 16 mass%, in 100 mass% of the constituent components (monomer units) of the acrylic copolymer.
[0065] Specific examples of the (meth)acrylic acid alkyl ester (a2) having an alkyl group having 4 to 12 carbon atoms include butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, and lauryl (meth)acrylate. Among these, 2-ethylhexyl (meth)acrylate is preferred. The content of the (meth)acrylic acid alkyl ester (a2) is 50 to 80 mass%, preferably 65 to 79 mass%, in 100 mass% of the constituent components (monomer units) of the acrylic copolymer.
[0066] Specific examples of the carboxyl group-containing monomer (a3) include acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, 2-carboxy-1-butene, 2-carboxy-1-pentene, 2-carboxy-1-hexene, and 2-carboxy-1-heptene. The content of the carboxyl group-containing monomer (a3) is 10 to 15% by mass, and preferably 10 to 12% by mass, in 100% by mass of the constituent components (monomer units) of the acrylic copolymer.
[0067] Specific examples of the hydroxyl group-containing monomer (a4) include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. The content of the hydroxyl group-containing monomer (a4) is 0.01 to 0.5 mass%, and preferably 0.05 to 0.15 mass%, in 100 mass% of the constituent components (monomer units) of the acrylic copolymer.
[0068] The content of vinyl acetate (a5) is from 1 to 5 mass %, and preferably from 2 to 4 mass %, in 100 mass % of the constituent components (monomer units) of the acrylic copolymer.
[0069] The acrylic copolymer is obtained by copolymerizing at least the above-described components (a1) to (a5). The polymerization method is not particularly limited, but radical solution polymerization is preferred from the viewpoint of easy polymer design. Alternatively, an acrylic syrup consisting of the acrylic copolymer and its monomer may be first prepared, and then a crosslinking agent and an additional photopolymerization initiator may be added to the acrylic syrup for polymerization.
[0070] In producing the acrylic copolymer, monomers other than the components (a1) to (a5) may be copolymerized within the limits that do not impair the effects of the present invention.
[0071] A crosslinking agent having reactivity with the functional group of the acrylic copolymer is generally used for the acrylic adhesive. Examples of the crosslinking agent include isocyanate compounds, acid anhydrides, amine compounds, epoxy compounds, metal chelates, aziridine compounds, and melamine compounds. The amount of the crosslinking agent added is usually 0.01 to 5 parts by mass, preferably 0.02 to 1 part by mass, and more preferably 0.3 to 0.6 parts by mass, based on 100 parts by mass of the acrylic copolymer. In addition, in order to ensure the adhesive strength required for temporary fixation, the peak temperature of tan δ of the acrylic adhesive used in the adhesive region (A2R) is preferably 20°C or less, more preferably -50°C to 10°C.
[0072] If necessary, the acrylic adhesive may contain silane coupling agents, tackifier resins such as rosin, terpene, petroleum, coumarone-indene, pure monomer, phenol, and xylene, softeners including mineral oils such as paraffin process oil, polyester plasticizers, and vegetable oils, and antioxidants such as aromatic secondary amines, monophenols, bisphenols, polyphenols, benzimidazoles, and phosphorous acid. Saturated hydrocarbon resins may also be added.
[0073] The type of rubber-based adhesive is not particularly limited, and various known rubber-based adhesives having a rubber component as the main component can be used. Specific examples of rubber components include synthetic rubbers such as butyl rubber, polyisobutylene rubber, isoprene rubber, styrene-isobutylene-styrene block copolymer, styrene-isoprene block copolymer, styrene-butadiene rubber, styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene-styrene block copolymer, styrene-ethylene-propylene-styrene block copolymer, and styrene-ethylene-propylene block copolymer; and natural rubber. Two or more kinds of rubber components may be used in combination. Butyl rubber is generally a rubber whose main component is a copolymer of isobutylene and 1 to 3 mass% of isoprene.
[0074] When a rubber-based adhesive is used in the adhesive region (A2R), the adhesive composition constituting the adhesive region (A2R) preferably contains a saturated hydrocarbon resin together with the rubber-based adhesive. The saturated hydrocarbon resin is a hydrocarbon resin that does not have an unsaturated bond, and is a component for improving the adhesiveness of the adhesive region (A2R).
[0075] The type of saturated hydrocarbon resin is not particularly limited, and for example, various alicyclic or aliphatic saturated hydrocarbon resins known as tackifiers can be used. Two or more saturated hydrocarbon resins may be used in combination. In particular, alicyclic saturated hydrocarbon resins are preferred, and hydrocarbon resins in which unsaturated bonds have been eliminated by hydrogenation treatment are more preferred. Commercially available saturated hydrocarbon resins include hydrogenated petroleum resins. Hydrogenated petroleum resins are resins obtained by hydrogenating petroleum resins (e.g., aromatic petroleum resins, aliphatic petroleum resins, copolymerized petroleum resins of alicyclic and aromatic components, etc.). Among these, hydrogenated petroleum resins (alicyclic saturated hydrocarbon resins) obtained by hydrogenating aromatic petroleum resins are preferred. Preferred hydrogenated petroleum resins are available as commercial products (e.g., Arcon (registered trademark) P-100, manufactured by Arakawa Chemical Industries, Ltd.). The content of the saturated hydrocarbon resin is preferably 0.01 to 100 parts by mass, more preferably 0.01 to 80 parts by mass, relative to 100 parts by mass of the adhesive component. The higher the content of the saturated hydrocarbon resin, the more improved the adhesiveness. In addition, in order to ensure the adhesive strength required for temporary fixation, the peak temperature of tan δ of the rubber-based adhesive used in the adhesive region (A2R) is preferably −10° C. or lower, more preferably −20° C. to 10° C.
[0076] The type of silicone-based adhesive is not particularly limited, and various known silicone-based adhesives containing a silicone component as a main component can be used. Examples of silicone components include silicone rubber and silicone resin containing organopolysiloxane as a main component. A catalyst such as a platinum catalyst, a crosslinking agent such as a siloxane crosslinking agent, or a peroxide crosslinking agent can be added to such a silicone component to crosslink and polymerize it. The saturated hydrocarbon resin mentioned above may be blended. In addition, in order to ensure the adhesive strength required for temporary fixation, the peak temperature of tan δ of the silicone-based adhesive used in the adhesive region (A2R) is preferably 70°C or less, more preferably 50°C or less.
[0077] Each of the pressure-sensitive adhesives described above may further contain other components as necessary, such as a solvent such as toluene, additives such as antioxidants, ultraviolet absorbers, light stabilizers, and antistatic agents, and fillers or pigments such as carbon black, calcium oxide, magnesium oxide, silica, zinc oxide, and titanium oxide.
[0078] [Base material] The substrate in the present invention is not particularly limited, but is preferably a heat-resistant insulating substrate. The level of heat resistance varies depending on the application, but for example, the melting temperature of the substrate is preferably 200°C or higher, more preferably 250°C or higher. For example, the continuous use temperature of the substrate measured in accordance with UL-746B is preferably 100°C or higher, more preferably 150°C or higher.
[0079] The substrate may be a single-layer substrate made of one member, or a substrate made of a laminate having a laminate structure in which one member and another member are bonded together with a bonding adhesive. The substrate may have flexibility or resilience, and the properties are appropriately selected depending on the application.
[0080] The material constituting the substrate is not particularly limited, but is preferably a resin film, a nonwoven fabric, or paper, and more preferably a resin film. When the substrate is a substrate made of a laminate, the material is preferably one or more members selected from the group consisting of a resin film, a nonwoven fabric, and paper, and more preferably at least one of the members is a resin film.
[0081] Specific examples of the resin film include polyester-based resins such as polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate (PEN), and aromatic polyester; polycarbonate; polyarylate; polyurethane; polyamide-based resins such as polyamide and polyetheramide; polyimide-based resins such as polyimide, polyetherimide, and polyamideimide; polysulfone-based resins such as polysulfone and polyethersulfone; polyetherketone-based resins such as polyetherketone and polyetheretherketone; polyphenylene sulfide (PPS); and modified polyphenylene oxide. Two or more types of resin films may be used in combination. Among them, polyphenylene sulfide (PPS), polyethylene naphthalate (PEN), polyimide, and polyetheretherketone are preferred.
[0082] The substrate may be subjected to a corona treatment or a primer treatment in order to improve adhesion to the adhesive layer (A1L).
[0083] The thickness of the substrate may be appropriately selected depending on the intended use, and is generally 2 to 200 μm, preferably 9 to 100 μm, and more preferably 12 to 100 μm.
[0084] [Release layer] The adhesive sheet of the present invention may have a release layer. Specific examples of the release agent include organic heat-melting resins such as silicone, paraffin, and long-chain alkyl compounds, non-silicone and silicone-modified aminoalkyd thermosetting resins, calcium carbonate, and inorganic fine particles such as silicon oxide fine particles. Among them, long-chain alkyl compounds and alkyd thermosetting resins are preferred from the viewpoint of the storage stability and adhesiveness of the adhesive sheet. Organic or inorganic oils are not preferred because they contaminate the production line and use line of the adhesive sheet and also significantly reduce the adhesiveness of the adhesive layer (A1L).
[0085] As the long-chain alkyl compound, a commercially available long-chain alkyl release agent can be used. For example, there is "Peiroil (registered trademark) 1010" (manufactured by Lion Specialty Chemicals), which is an organic solvent-soluble long-chain alkyl release agent, and "NC003" (manufactured by Chukyo Yushi), which is a water-dispersible long-chain alkyl release agent. To apply a thin film of a water-dispersible long-chain alkyl compound to the surface of a layer with a relatively low polarity such as an epoxy adhesive layer, it is preferable to use an appropriate wettability improver. A specific example of a wettability improver is acetylene diol.
[0086] Examples of alkyd-based compounds include commercially available "Tesfine (registered trademark) 303," "Tesfine 305," "Tesfine 314," and "Tesfine 319" (manufactured by Showa Denko Materials).
[0087] The long-chain alkyl release agent may be diluted with a solvent to a suitable concentration and applied so that the thickness of the release layer after drying is preferably 0.02 to 0.2 μm. The alkyd resin release agent may be diluted with a solvent to a suitable concentration and applied so that the thickness of the release layer after drying is preferably 0.02 to 2 μm.
[0088] [Adhesive sheet] The adhesive sheet of the present invention is an adhesive sheet having the above-described adhesive region (A2R), more specifically, an adhesive sheet having an adhesive region (A2R) formed by partially providing an adhesive (A2) on at least one surface of an adhesive layer (A1L), and an area on the surface where the adhesive region (A2R) is not formed is an adhesive layer exposed area (A1LR). The adhesive sheet of the present invention may be a baseless type adhesive sheet having no substrate, a single-sided adhesive sheet, or a double-sided adhesive sheet.
[0089] A release film may be provided on the outermost layer of the adhesive sheet of the present invention, for example, on the adhesive layer (A1L), the pressure-sensitive adhesive region (A2R) or the release layer.
[0090] The release film is not particularly limited, but examples include fine paper, craft paper, glassine paper, polyester film, polyolefin film, etc., treated with a release agent, fine paper, craft paper, glassine paper, etc., laminated with polyethylene or the like and treated with a release agent, and untreated polyolefin film or polyether ether ketone film.
[0091] The adhesive sheet of the present invention has a thickness before heat curing of, for example, 10 to 1000 μm. When the adhesive sheet of the present invention is used for bonding narrow gaps, the thickness before heat curing is preferably 250 μm or less, more preferably 20 to 200 μm.
[0092] The method of manufacturing the adhesive sheet of the present invention is not particularly limited. For example, a baseless type adhesive sheet as shown in FIG. 1(a) can be manufactured by forming an adhesive layer (A1L) on the surface of a separator, and then laminating a pressure-sensitive adhesive region (A2R) on one side of the adhesive layer (A1L). An adhesive sheet having a release layer as shown in FIG. 1(d) can be manufactured by forming an adhesive layer (A1L) on the surface of a separator, performing a release treatment on one side to form a release layer, then peeling off the separator, and laminating a pressure-sensitive adhesive region (A2R) on that surface. A double-sided adhesive sheet as shown in FIG. 1(e) etc. can be manufactured by forming an adhesive layer (A1L) on the surface of a separator, laminating it on both sides of a substrate, peeling off the separator of one side of the adhesive layer (A1L), and laminating a pressure-sensitive adhesive region (A2R) on that surface. A double-sided adhesive sheet having a release layer as shown in Figure 1(h) can be produced by peeling off the separator from the adhesive layer (A1L) on the other side and performing a release treatment to form a release layer. A double-sided adhesive sheet having adhesive regions (A2R) on both sides as shown in Figure 1(i) can be produced by peeling off the separator from the adhesive layer (A1L) on both sides and bonding the adhesive regions (A2R). However, other methods are also possible.
[0093] The adhesive region (A2R) can be formed, for example, by gravure printing onto a separator in a desired pattern as shown in Fig. 2, followed by curing and drying. As shown in Fig. 1(b) and Fig. 1(f), an adhesive sheet in which the outer surface of the adhesive region (A2R) is approximately flush with the outer surface of the adhesive layer exposed region (A1LR) can be produced by heat laminating the adhesive region (A2R) to the adhesive layer (A1L).
[0094] The adhesive layer (A1L) can be formed by a conventional method such as a solution coating method, a melt coating method, a melt extrusion method, a rolling method, etc. The melt coating method can be performed without a solvent, and does not require a solvent removal step or treatment equipment, etc., so it is preferable in terms of productivity and economy. When using the melt coating method, it is preferable that the epoxy resin contains a crystalline epoxy resin. In this case, by heating to a temperature above the melting point of the crystalline epoxy resin, the melt viscosity of the epoxy resin can be reduced and the melt coating speed can be increased. EXAMPLES
[0095] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these. In the following description, "parts" means parts by mass.
[0096] <Adhesive (A1)> The following components were mixed in the amounts (parts) shown in Table 1 to obtain an adhesive.
[0097] [Epoxy resin] "E1": Phenol novolac type epoxy resin (softening point 92°C, epoxy equivalent 218g / eq) "E2": Phenol novolac type epoxy resin (semi-solid, epoxy equivalent 180g / eq) "E3": Polypropylene glycol diglycidyl ether type epoxy resin (liquid, epoxy equivalent 315g / eq) "E4": Polyglycidylamine type epoxy resin (liquid, epoxy equivalent 112g / eq)
[0098] [Hardening agent] "C1": Triphenylmethane type phenolic resin (softening point 110°C, hydroxyl equivalent 97g / eq) "C2": Dicyandiamide (manufactured by Mitsubishi Chemical Corporation, product name DICY7)
[0099] [Elastomer] "ER": Linear polyester polyurethane resin (softening point 87°C, molecular weight 222300, hydroxyl group content 0.1%)
[0100] [Filler] "F": Magnesium silicate (average particle size 5 μm)
[0101] [Foaming agent] "H": Thermally expandable microcapsules (average particle size 15 μm, expansion start temperature 125-135°C, maximum expansion temperature 150-160°C)
[0102] [Cure accelerator] "S1": 2-phenyl-4,5-dihydroxymethylimidazole (manufactured by Shikoku Chemical Industry Co., Ltd., product name 2PHZ-PW) "S2": 2,4-diamino-6-[2'-methylimidazole-(1')]-ethyl-s-triazine isocyanuric acid adduct (manufactured by Shikoku Chemical Industry Co., Ltd., product name 2MAOK-PW)
[0103] [solvent] "MEK": Methyl ethyl ketone
[0104] [Table 1]
[0105] <Adhesive (A2)> (Preparation of Acrylic Copolymer) A reactor equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 13% by mass of methyl acrylate, 70% by mass of 2-ethylhexyl acrylate, 4.9% by mass of n-butyl acrylate, 10% by mass of acrylic acid, 0.1% by mass of 4-hydroxybutyl acrylate, 2% by mass of vinyl acetate, ethyl acetate, n-dodecanethiol as a chain transfer agent and 0.1 parts of lauryl peroxide as a peroxide radical polymerization initiator. Nitrogen gas was sealed in the reactor, and polymerization reaction was carried out at 68°C for 3 hours under nitrogen gas flow while stirring, and then at 78°C for 3 hours. After that, it was cooled to room temperature and ethyl acetate was added. As a result, an acrylic copolymer with a solid content concentration of 30% was obtained. The weight average molecular weight (Mw) of the acrylic copolymer was 1 million, and the theoretical Tg was -62°C.
[0106] The weight average molecular weight (Mw) of the acrylic copolymer is a value obtained by measuring the molecular weight of the acrylic copolymer in terms of standard polystyrene by a GPC method using the following measuring device and conditions. Equipment: LC-2000 series (JASCO Corporation) Columns: Shodex KF-806M x 2, Shodex KF-802 x 1 Eluent: Tetrahydrofuran (THF) ·Flow rate: 1.0mL / min Column temperature: 40℃ ·Injection volume: 100μL Detector: Refractometer (RI) Measurement sample: An acrylic polymer was dissolved in THF to prepare a solution with an acrylic polymer concentration of 0.5% by mass, and then filtered to remove any impurities.
[0107] The theoretical Tg of the acrylic copolymer is a value calculated according to the FOX formula.
[0108] (Preparation of Acrylic Pressure-Sensitive Adhesive Composition) To 100 parts of the solid content of the acrylic copolymer, 0.48 parts of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, product name: Coronate (registered trademark) L-45E), 0.15 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBM-403), and 0.07 parts of an antioxidant (manufactured by BASF, product name: Irganox (registered trademark) 1010) were added and mixed to prepare an acrylic adhesive composition (adhesive (A2)). The peak temperature of tan δ of this acrylic adhesive composition was 2°C.
[0109] <Formation of adhesive area (A2R)> (Fig. 2(a) type) The acrylic adhesive composition obtained as described above was applied by gravure printing onto a release-treated PET film (release film) in a pattern in which round island-shaped adhesive regions (A2R) were regularly arranged in horizontal rows at half-shifted positions as shown in Figure 2(a), and the composition was cured and dried to form adhesive regions (A2R) with a thickness of 1 μm. This resulted in a sheet for forming adhesive regions (A2R) of the type shown in Figure 2(a).
[0110] The diameter of this round island-shaped adhesive region (A2R) was 1.0 mm, and the width of the exposed adhesive region (A1LR) was 0.25 mm. The ratio of the area of the adhesive region (A2R) to the total area (100%) of the areas of the adhesive region (A2R) and the exposed adhesive region (A1LR) was 58%.
[0111] (Fig. 2(b) type) The acrylic adhesive composition obtained as described above was applied by gravure printing onto a release-treated PET film in a pattern in which square island-shaped adhesive regions (A2R) were regularly arranged in vertical rows at equal intervals as shown in Figure 2(b), and the film was cured and dried to form adhesive regions (A2R) with a thickness of 2 μm. This resulted in a sheet for forming adhesive regions (A2R) of the type shown in Figure 2(b).
[0112] The square island-shaped adhesive region (A2R) was a square with sides of 1.2 mm, and the width of the exposed adhesive layer region (A1LR) was 0.3 mm. In this case, the ratio of the area of the adhesive region (A2R) to the total area (100%) of the areas of the adhesive region (A2R) and the exposed adhesive layer region (A1LR) was 64%.
[0113] <Example 1> A solution of adhesive (A1) (blending 1) was applied to a silicone-treated PET film (release film) so that the adhesive thickness after drying would be 60 μm, and then dried to obtain a sheet for forming an adhesive layer (A1L).
[0114] A 25 μm thick PPS film (manufactured by Toray Industries, Inc.) was prepared as a substrate. The adhesive layer (A1L) side of the adhesive layer (A1L) forming sheet obtained as described above was laminated on each side of this substrate. This allowed the formation of a 60 μm thick adhesive layer (A1L) on both sides of the substrate.
[0115] Next, the PET film (release film) on one side was peeled off, and the adhesive area (A2R) side of the adhesive area (A2R) forming sheet of the type of FIG. 2(a) prepared previously was laminated. This allowed the adhesive area (A2R) of FIG. 2(a) to be formed on the outer surface of one adhesive layer (A1L). The structure of the adhesive sheet obtained in this example corresponds to the structure shown in FIG. 1(a).
[0116] <Example 2> An adhesive sheet was prepared in the same manner as in Example 1, except that the width of the adhesive layer exposed region (A1LR) was increased and the ratio of the area of the adhesive region (A2R) to the total area (100%) of the area of the pressure-sensitive adhesive region (A2R) and the area of the adhesive layer exposed region (A1LR) was changed to 1%.
[0117] <Example 3> An adhesive sheet was prepared in the same manner as in Example 1, except that a sheet for forming an adhesive region (A2R) of FIG. 2(b) was used instead of a sheet for forming an adhesive region (A2R) of FIG. 2(a).
[0118] <Example 4> An adhesive sheet was produced in the same manner as in Example 1, except that a solution of adhesive (A1) of Blend 2 (a solution not containing a foaming agent) was used instead of the solution of adhesive (A1) of Blend 1. The structure of the adhesive sheet obtained in this example corresponds to the structure shown in FIG. 1(g).
[0119] <Example 5>
[0120] An adhesive sheet was produced in the same manner as in Example 1, except that the PET film (release film) on the adhesive layer (A1L) on which the pressure-sensitive adhesive region (A2R) was not formed was peeled off and a release treatment was performed to form a release layer. The structure of the adhesive sheet obtained in this example corresponds to the structure shown in FIG. 1(h).
[0121] Specifically, this release layer was formed by applying a mixture of 5.71% by weight of Tesfine (registered trademark) 305 (manufactured by Showa Denko Materials), 0.14% by weight of Dryer 900 (manufactured by Showa Denko Materials), 75.35% by weight of isopropyl alcohol, and 18.8% by weight of toluene with a Meyer bar #5 and drying it.
[0122] <Example 6> Except for forming a pressure-sensitive adhesive region (A2R) in both of the two adhesive layers (A1L), an adhesive sheet was produced in the same manner as in Example 1. The structure of the adhesive sheet obtained in this example corresponds to the structure shown in FIG. 1(f).
[0123] <Example 7> A solution of adhesive (A1) (mixture 1) was applied to a silicone-treated PET film (release film) so that the adhesive thickness after drying was 60 μm, and then dried to form an adhesive layer (A1L). The adhesive region (A2R) side of the adhesive region (A2R) forming sheet of FIG. 2(a) type was laminated to one side of this adhesive layer (A1L) in the same manner as in Example 1. This allowed the adhesive region (A2R) of FIG. 2(a) type to be formed on one side of the adhesive layer (A1L). The structure of the adhesive sheet obtained in this example corresponds to the structure shown in FIG. 1(a) (baseless type without a substrate).
[0124] <Example 8> An adhesive sheet was produced in the same manner as in Example 1, except that a solution of adhesive (A1) of Blend 3 was used instead of the solution of adhesive (A1) of Blend 1.
[0125] <Example 9> An adhesive sheet was produced in the same manner as in Example 1, except that a solution of adhesive (A1) of Blend 4 was used instead of the solution of adhesive (A1) of Blend 1.
[0126] <Example 10> An adhesive sheet was produced in the same manner as in Example 1, except that the adhesive region (A2R) forming sheet of the type shown in Figure 2(a) was laminated while being heated using a thermal laminator (set temperature 110°C) so that the outer surface of the adhesive region (A2R) and the outer surface of the adhesive layer exposed region (A1LR) were formed to be on approximately the same plane. The structure of the adhesive sheet obtained in this example corresponds to the structure shown in Figure 1(b).
[0127] <Comparative Example 1> An adhesive sheet was prepared in the same manner as in Example 1, except that the adhesive region (A2R) forming sheet of FIG. 2(a) type was not used, and instead an acrylic adhesive composition (adhesive (A2)) was applied to the entire outer surface of one adhesive layer (A1L).
[0128] <Comparative Example 2> An adhesive sheet was produced in the same manner as in Example 1, except that the pressure-sensitive adhesive region (A2R) was not formed.
[0129] <Comparative Example 3> An adhesive sheet was produced in the same manner as in Comparative Example 2, except that a solution of adhesive (A1) of Blend 5 was used instead of the solution of adhesive (A1) of Blend 1.
[0130] <Comparative Example 4> An adhesive sheet was produced in the same manner as in Comparative Example 2, except that a solution of adhesive (A1) of Blend 6 was used instead of the solution of adhesive (A1) of Blend 1.
[0131] <Comparative Example 5> An adhesive sheet was prepared in the same manner as in Example 1, except that the adhesive region (A2R) forming sheet of FIG. 2(a) type was not used, and instead an acrylic adhesive composition (adhesive (A2)) was applied to the entire surface of the outer surfaces of the two adhesive layers (A1L).
[0132] The adhesive sheets of Examples 1 to 10 and Comparative Examples 1 to 5 were evaluated according to the following methods. The results are shown in Tables 2 to 4.
[0133] [Peak temperature of tan δ of adhesive (A1)] Using a viscoelasticity testing machine for dynamic viscoelasticity measurements, an adhesive sample approximately 2 mm thick was sandwiched between the parallel plates of the measuring section of the testing machine, and the storage modulus G' and loss modulus G'' were measured at a frequency of 10 Hz and at temperatures between -20°C and 100°C. Tan δ was calculated using the formula tan δ (loss factor) = G'' / G', and the peak temperature was analyzed.
[0134] [Stickiness at low temperatures (temporary fixation)] In a 5°C environment, a 20 mm square sheet was pressed onto a polished SUS plate with a 2 kg roller, and after 10 seconds the SUS plate was lifted and turned over, and the sheet was evaluated according to the following criteria. "○": The sheet did not fall off. "X": The sheet fell off.
[0135] [Adhesion maintenance rate (200℃)] The shear adhesive strength of an adhesive sheet with an adhesive region (A2R) and an adhesive sheet without an adhesive region (A2R) when heated at 200°C was measured, and the strength ratio of the sheet with an adhesive region (A2R) to the strength of the sheet without an adhesive region (A2R) was calculated using the following formula, assuming the strength to be 100%. (Shear strength when heated with adhesive region (A2R)) ÷ (Shear strength when heated without adhesive region (A2R)) × 100
[0136] The shear adhesive strength was measured by the following method. An adhesive sheet (10 mm square) was attached to an SPCC plate, spacers of a specified thickness were placed on the left and right sides, and an SPCC plate was placed on top of that, the spacers were secured with clips, and the plate was cured by heating for 20 minutes in a hot air dryer at 170°C. The strength of the prepared test piece was measured by pulling it at a speed of 50 mm / min in a tensile tester with a thermostatic chamber set to 200°C.
[0137] The spacer thickness was 300 μm in Examples 1 to 3, 5, 6, 8 to 10 and Comparative Examples 1 to 4, 100 μm in Example 7, and 0 μm in Example 4 and Comparative Example 5.
[0138] [Resin flow resistance] A 10 mm square adhesive sheet is sandwiched between glass plates, a 500 g weight is placed on top, and the amount of resin that protrudes after 1 hour at 40°C is measured with a vernier caliper. (Resin width after test) - (Resin width before test (sheet width))
[0139] [Life (stickiness at low temperatures)] The adhesive sheet was stored at 40°C for one day, and then a "low temperature adhesion" test was carried out and evaluated according to the following criteria. "○": The sheet did not fall off. "X": The sheet fell off.
[0140] [Table 2]
[0141] [Table 3]
[0142] [Table 4]
[0143] As is clear from the evaluation results in Tables 2 to 4, in Examples 1 to 10 in which the adhesive sheets of the present invention were used, all of the properties were excellent.
[0144] On the other hand, the adhesive sheet of Comparative Example 1, in which the adhesive (A2) was applied over the entire surface, had a lower adhesive retention rate (200°C) and poorer heat resistance than the adhesive sheets of Examples 1 to 3, in which the adhesive layer (A1L) of the same composition had a partial adhesive region (A2R) provided thereon. Similarly, the adhesive sheet of Comparative Example 5 had a lower adhesive retention rate (200°C) and poorer heat resistance than the adhesive sheet of Example 4. This is thought to be because, in the case of the adhesive sheets of Comparative Examples 1 and 5, in the absence of an adhesive layer exposed region (A1LR), the fluidity of the adhesive is hindered during heat curing, making it difficult for the adhesive to reach the adherend, and stable high adhesive strength cannot be obtained.
[0145] Conversely, among the adhesive sheets of Comparative Examples 2 to 4 that did not include the adhesive (A2), Comparative Example 2 had poor adhesion (temporary fixation) at low temperatures. This is believed to be because the adhesive layer (A1L) used an adhesive (Formulation 1) that was solid and did not show tack at 5°C. On the other hand, the adhesive sheets of Comparative Examples 3 and 4 used adhesives (Formulations 5 and 6) that showed tack at 5°C, so that they had excellent adhesion (temporary fixation) at low temperatures even without the adhesive region (A2R). However, the adhesive sheet of Comparative Example 3 had poor life (adhesion at low temperatures after storage at 40°C for 1 day). This is believed to be because the adhesive of Formulation 5 used an epoxy resin that was multifunctional and highly reactive. In addition, the adhesive sheet of Comparative Example 4 had poor resin flow resistance. This is believed to be because the peak temperature of tan δ of the adhesive of Formulation 6 was low at "-3°C", resulting in poor shape stability. [Industrial Applicability]
[0146] The adhesive sheet of the present invention has excellent handleability because it has the adhesive strength required for temporary fixation when applied, and also maintains a stable high adhesive strength after heat curing, and has excellent heat resistance. Therefore, it is useful, for example, for inserting an industrial part into a narrow part of another industrial part and adhesively fixing it. [Explanation of symbols]
[0147] A1L adhesive layer A2R Adhesive Field A1LR Adhesive layer exposed area 10. Substrate 11 Release layer
Claims
1. An adhesive sheet having an adhesive layer (A1L) that is solid at 18°C, The adhesive layer (A1L) contains an epoxy resin, The adhesive layer (A1L) further contains a temperature-sensitive foaming agent, The temperature-sensitive foaming agent is a thermally expandable microcapsule, a pressure-sensitive adhesive region (A2R) formed by partially providing a pressure-sensitive adhesive (A2) on at least one surface of the adhesive layer (A1L); the pressure-sensitive adhesive (A2) is selected from the group consisting of an acrylic pressure-sensitive adhesive, a rubber pressure-sensitive adhesive, a silicone pressure-sensitive adhesive, and any combination thereof; the acrylic pressure-sensitive adhesive has a peak tan δ temperature of 20° C. or less, the rubber pressure-sensitive adhesive has a peak tan δ temperature of −10° C. or less, and the silicone pressure-sensitive adhesive has a peak tan δ temperature of 70° C. or less; An adhesive sheet in which the area on the surface where the pressure-sensitive adhesive area (A2R) is not formed is an adhesive layer exposed area (A1LR) where the surface of the adhesive layer (A1L) is exposed.
2. The adhesive sheet according to claim 1 , wherein the adhesive layer (A1L) exhibits no tack at 5° C.
3. 2. The adhesive sheet according to claim 1, wherein the ratio of the area of the adhesive region (A2R) to the total area (100%) of the area of the adhesive region (A2R) and the area of the exposed adhesive layer region (A1LR) is 1% to 70%.
4. 2. The adhesive sheet according to claim 1, wherein the outer surface of the pressure-sensitive adhesive region (A2R) protrudes outward beyond the outer surface of the adhesive layer exposed region (A1LR).
5. 2. The adhesive sheet according to claim 1, wherein the outer surface of the pressure-sensitive adhesive region (A2R) and the outer surface of the adhesive layer exposed region (A1LR) are substantially flush with each other.
6. 2. The adhesive sheet according to claim 1, which has a pressure-sensitive adhesive region (A2R) on one side of the adhesive layer (A1L) and a substrate on the other side of the adhesive layer (A1L).
Citation Information
Patent Citations
Thermosetting self-adhesive article in sheet form
JP1991014888A
Adhesive tape for structural bonding
JP2007518865A
Adhesive sheet
JP2016084470A
Tape for wafer processing
JP2017005160A
Adhesive, metal member assembly, and method of manufacturing metal member assembly
JP2017203114A